2014
DOI: 10.1111/iej.12231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pulp response to mineral trioxide aggregate and a bioceramic paste in partial pulpotomy of sound human premolars: a randomized controlled trial

Abstract: When treating teeth with healthy pulps, the response to partial pulpotomy treatment with both MTA and iRoot BP was favourable. However, pulps covered with iRoot BP were more sensitive to cold stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…, Azimi et al . ). Although the results varied according to dilution and time period, they revealed a similar cell viability of iRoot BP compared to WMTA.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…, Azimi et al . ). Although the results varied according to dilution and time period, they revealed a similar cell viability of iRoot BP compared to WMTA.…”
Section: Discussionmentioning
confidence: 97%
“…This study evaluated the cytotoxicity and effects of iRoot BP and WMTA on the expression of mineralization-related genes. The in vitro cytotoxicity of the materials was evaluated by XTT assay, a standard assay of cytotoxicity and cell survival (Koulaouzidou et al 2008, De-Deus et al 2009, Damas et al 2011, Azimi et al 2014. Although the results varied according to dilution and time period, they revealed a similar cell viability of iRoot BP compared to WMTA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies involving other bioceramic endodontic sealers already revealed hard tissue deposition 29 and favorable tissue response to partial pulpotomy. 30 Monobasic calcium phosphates are included in the sealer to facilitate the reaction with calcium hydroxide to produce water and hydroxyapatite upon activation of the sealer by water. 31 Previous studies on bioceramic sealers have revealed lower inflammatory mediators and better osteoblast expression, thus indicating that the bioceramic is biocompatible.…”
Section: Discussionmentioning
confidence: 99%